Food Security in Sabah: An Overview for Rice Self Sufficient Target Rafiq Idris - rafiq idris (Saspublisher, 2018)
Food security in terms of food sufficiency has become a concern and subject of  interest  in  Malaysia.  Malaysia  as  a  whole  and  Sabah  in  particular  is  not  self-sufficient in terms of rice production for its own population. Sabah as a land abundant state  does import rice  from neighbouring countries to  fulfil its domestic demand. This paper  estimates  the  level  of  rice  supply  in  Sabah  before  Malaysian  formation  and present  for  each  single  people  in  the  state.  Several  ratio  such  as  the  production-per capita  (PPC),  consumption  per-capita  (CPC),  import  dependency  ratio  (IDR)  and  self-sufficiency  ratio  (SSR)  are  being  computed  to  estimate  the  self-sufficient  level.  In addition, this paper highlights that Sabah should improve its self-sufficient position.